Analysis for effects of electrolyte level on energy consumption in magnesium electrolysis by finite element method. (3rd November 2016) - Sun, Ze; Cai, Liwei; Liu, Chenglin; Lu, Guimin; Yu, Jianguo
ABSTRACT: In the process of magnesium electrolysis, increasing the level of electrolyte can reduce the cell voltage and energy consumption in an electrolysis magnesium cell. In this paper, a three‐dimensional model of a full cell was implemented to study the relationship between the cell voltage and electrolyte level in a magnesium electrolysis cell. Firstly, the resistance voltage of difference current intensity in magnesium electrolysis cells were discussed with the electrolyte depth from 1.25 to 1.45 m. Moreover, the size of anodes and positions of anodes and cathodes were changed to investigate the trend of resistance voltage in the cell. The energy consumption in each part of the electrolyte was integrated to further understand the energy distribution in the electrolyte to explore which part of the electrolyte has the greatest contribution to the cell voltage. Through analyzing components of the cell voltage, energy distribution, and thermal balance, the explanation of the relationship between electrolyte level and energy consumption can be obtained.